Intellectual Humility as Attitude. (4th August 2016) - Tanesini, Alessandra
Abstract : Intellectual humility, I argue in this paper, is a cluster of strong attitudes (as these are understood in social psychology) directed toward one's cognitive make‐up and its components, together with the cognitive and affective states that constitute their contents or bases, which serve knowledge and value‐expressive functions. In order to defend this new account of humility I first examine two simpler traits: intellectual self‐acceptance of epistemic limitations and intellectual modesty about epistemic successes. The position defended here addresses the shortcomings of both ignorance and accuracy based accounts of humility.